Persistent suppression of subthalamic beta-band activity during rhythmic finger tapping in Parkinson's disease. - Joundi, R; Brittain, J; Green, A; Aziz, T; Brown, P; Jenkinson, N (2013)
OBJECTIVE: The function of synchronous oscillatory activity at beta band (15-30Hz) frequencies within the basal ganglia is unclear. Here we sought support for the hypothesis that beta activity has a global function within the basal ganglia and is not directly involved in the coding of specific biomechanical parameters of movement. METHODS: We recorded local field potential activity from the subthalamic nuclei of 11 patients with Parkinson's disease during a synchronized tapping task at three different externally cued rates. RESULTS: Beta activity was suppressed during tapping, reaching a minimum that differed little across the different tapping rates despite an increase in velocity of finger movements. Thus beta power suppression was independent of specific motor parameters. Moreover, although beta oscillations remained suppressed during all tapping rates, periods of resynchronization between taps were markedly attenuated during high rate tapping. As such, a beta rebound above baseline between taps at the lower rates was absent at the high rate. CONCLUSION: Our results demonstrate that beta desynchronization in the region of the subthalamic nucleus is independent of motor parameters and that the beta resynchronization is differentially modulated by rate of finger tapping, SIGNIFICANCE: These findings implicate consistent beta suppression in the facilitation of continuous movement sequences.